2008
DOI: 10.1002/ppul.20866
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysregulation in young girls with Rett Syndrome during nighttime in‐home recordings

Abstract: This study was designed to specifically characterize the autonomic phenotype of cardiorespiratory dysregulation during the nighttime in young girls with MECP2 mutation-confirmed Rett Syndrome (RS), studied in their home environment. Computerized breath-to-breath and beat-to-beat characterization of at-home continuously recorded respiratory inductance plethysmography of chest/abdomen and ECG (VivoMetrics, Inc.) was obtained during overnight recordings in 47 girls with MECP2 mutation-confirmed RS and 47 age-, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 20 publications
2
87
0
Order By: Relevance
“…In light of the fact that breathing dysfunction in RTT patients improves with relaxation or sleep (Weese-Mayer et al, 2008; Katz et al, 2009; Ren et al, 2012; Ramirez et al, 2013), we considered the possibility that, rather than, or in addition to, any direct effects on respiratory control per se, LM22A-4 might also improve breathing by inducing sedation. Indeed, other studies have shown that apneic breathing in RTT mouse models is reduced by drugs with sedating or anxiolytic effects, including the GABA uptake inhibitor NO-711 (Abdala et al, 2010), the GABA A partial agonist L838,417 (Abdala et al, 2010), the 5-HT1A antagonist 8-OH-DPAT (Abdala et al, 2010), the benzodiazepines midazolam (Voituron and Hilaire, 2011) and diazepam (Abdala et al, 2010), the norepinephrine uptake inhibitor desipramine (Roux et al, 2007; Zanella et al, 2008), and the corticotropin-releasing hormone receptor 1 antagonist antalarmin (Ren et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the fact that breathing dysfunction in RTT patients improves with relaxation or sleep (Weese-Mayer et al, 2008; Katz et al, 2009; Ren et al, 2012; Ramirez et al, 2013), we considered the possibility that, rather than, or in addition to, any direct effects on respiratory control per se, LM22A-4 might also improve breathing by inducing sedation. Indeed, other studies have shown that apneic breathing in RTT mouse models is reduced by drugs with sedating or anxiolytic effects, including the GABA uptake inhibitor NO-711 (Abdala et al, 2010), the GABA A partial agonist L838,417 (Abdala et al, 2010), the 5-HT1A antagonist 8-OH-DPAT (Abdala et al, 2010), the benzodiazepines midazolam (Voituron and Hilaire, 2011) and diazepam (Abdala et al, 2010), the norepinephrine uptake inhibitor desipramine (Roux et al, 2007; Zanella et al, 2008), and the corticotropin-releasing hormone receptor 1 antagonist antalarmin (Ren et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Various neurological conditions are associated with severe breathing disturbances. These disorders include multiple system atrophy (Schwarzacher et al, 2011), Rett syndrome (Ramirez et al, 2013b; Weese-Mayer et al, 2006, 2008b), Familial Dysautonomia (Carroll et al, 2012; Weese-Mayer et al, 2008a), sudden infant death syndrome (Garcia et al, 2013; Kinney et al, 2009; Paterson, 2013), congenital central hypoventilation syndrome (Ramanantsoa and Gallego, 2013), sleep apnea (Gozal and Kheirandish-Gozal, 2008; Ramirez et al, 2013a), Pitt Hopkins Syndrome (Gallego, 2012), and sudden death of epilepsy (Kalume, 2013; Sowers et al, 2013). Thus, understanding how breathing is generated within the nervous system and how the CNS controls ventilatory functions is of great clinical interest.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disruption is common in RTT patients (Glaze et al, 1987;Nomura, 2005;Young et al, 2007) with nighttime autonomic dysfunction also being reported later in the disease progression (Rohdin et al, 2007;Weese-Mayer et al, 2008). At least some of these sleep symptoms are disruptions in timing with RTT patients reporting difficulty sleeping at night and staying awake during the day, raising the possibility of an underlying circadian deficit.…”
mentioning
confidence: 97%